Potential modification of electrochemical properties in anode niobium pentoxide - Gomozov, V. P.; Deribo, S. G.; Skatkov, L. I.; Skrebtsova, S. S. (NTU "KhPI", 2008)
In the present work the technique for generation of electrochrome effect (ECE) in Nb₂O₅ amorphous anodic oxide films (AOF) is proposed. We have also found that when AOF is polarized by the packages of microsecond pulses, initial potential of gas emission can be increased three- to fivefold, which promotes significant increase in current density on film electrode, and, thus, raises the ECE.

У роботі запропонована методика формування анодних оксидних плівок Nb₂O₅, що володіють електрохромним ефектом (ЕХЕ). Встановлено, що поляризація оксидів пакетами мікросекундних імпульсів підвищує в 3-5 разів потенціал почала газовиділення і, таким чином, підвищує густину струму на електроді, інтенсифікуючи ЕХЕ.
Keywords: polycrystalline anode; electrochrome effect; slow surface states; polarization